Sagot :
Step-by-step solving: Equations Transformable into Quadratic Equations
Is it like this?
[tex]\frac{1}{3}x + \frac{4x}{6} =1[/tex]
[tex]6(\frac{1}{3}x + \frac{4x}{6} = 1)[/tex]
2x + 4x = 6
6x = 6
x = 1
or like this?
[tex]\frac{1}{3x} + \frac{4x}{6} = 1[/tex]
[tex]6x(\frac{1}{3x} + \frac{4x}{6} = 1)[/tex]
2 + 4x² = 6x
2 + 4x² - 6x = 0
4x² - 6x + 2 = 0
2x² - 3x + 1 = 0
2x² - x - 2x + 1 = 0
x(2x - 1) - (2x - 1) = 0
(x - 1)(2x - 1) = 0
x - 1 = 0
x = 1
2x - 1 = 0
2x = 1
x = [tex]\frac{1}{2}[/tex]